2018
DOI: 10.1007/s12144-018-9892-9
|View full text |Cite
|
Sign up to set email alerts
|

Traits and values as predictors of the frequency of everyday behavior: Comparison between models and levels

Abstract: The aims of this study were to compare (a) personality traits vs personal values, (b) Five-Factor Model (FFM) vs HEXACO model of personality traits, and (c) broad vs narrow personality constructs in terms of their relationship with the frequency of everyday behaviors. These relationships were analyzed at three organizational levels of self-reported behavior: (a) single behavioral acts, (b) behavioral components (empirically derived categories of similar behaviors), and (c) two higher-order factors. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 67 publications
(94 reference statements)
4
23
0
Order By: Relevance
“…Listening to music and reading correlated with openness also in previous studies (e.g. Skimina et al, ). Talking with friends can express Stimulation or Hedonism, as well as openness to new ideas.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Listening to music and reading correlated with openness also in previous studies (e.g. Skimina et al, ). Talking with friends can express Stimulation or Hedonism, as well as openness to new ideas.…”
Section: Discussionsupporting
confidence: 77%
“…For instance, Alessandri and Vecchione () showed that Stability accounted for variance in job performance beyond that of the Big Five. In a study conducted by Skimina et al (), Beta/Plasticity was related to surfing the Internet and game‐playing more strongly than any basic trait or facet of personality. Because the metatraits postulated by the Circumplex of Personality Metatraits reflect specific psychological meanings that go beyond the shared variance of lower‐level traits (Strus & Cieciuch, ), they should be good predictors of daily activities and situational context.…”
Section: Personality Metatraitsmentioning
confidence: 94%
See 2 more Smart Citations
“…As Keeney (1996) represents decisionmaking approach, he underlines that starting point for decision-making process are values primary expressed in the goals. Skimina, Cieciuch, & Strus (2018) assert that values reflect the content of the goals. On the whole, values represent the essential foundation for problem solving and could be integrated into it by several ways (see Figure 2).…”
Section: Problem Solving Integrating Value Approachmentioning
confidence: 99%